2022
DOI: 10.1186/s12879-022-07120-z
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity level and associated factors among adult HIV patients in Ethiopia

Abstract: Background People living with HIV, who take antiretroviral therapy (ART), often enjoy long and healthy lives, but this therapy has well known metabolic adverse effects. Physical activity is found to be an important factor in improving these physiological parameters. This study aimed to determine physical activity level and associated factors among HIV patients in Ethiopia. Methods An institutional based cross sectional study was conducted from May … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
1
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 22 publications
3
10
1
3
Order By: Relevance
“…However, the finding in the current study differed from the national study findings, which reported adults with higher education were 28% less likely to be physically active compared with those without formal education. 39 The possible variation could be due to differences in the source population in which the former study included participants from rural population where the majority of adults engage in agricultural related activities and use walking for travel to and from places due to limited transport access, 22 whereas the current study focused solely on urban adults.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the finding in the current study differed from the national study findings, which reported adults with higher education were 28% less likely to be physically active compared with those without formal education. 39 The possible variation could be due to differences in the source population in which the former study included participants from rural population where the majority of adults engage in agricultural related activities and use walking for travel to and from places due to limited transport access, 22 whereas the current study focused solely on urban adults.…”
Section: Discussionmentioning
confidence: 99%
“…20 21 Significant variability in reported inactivity levels reflects variation in studied populations, such as patient, adolescents or pregnant women. [22][23][24][25][26][27][28][29][30] The recommended level and intensity of physical activity varies for adults, adolescents, pregnant women and people living with different medical conditions. 3 Evidence on the level of physical activity and its predictors among adults in low-income countries, including Ethiopia, is sparse and inconclusive.…”
Section: Open Accessmentioning
confidence: 99%
“…Our study found that 46.2% of HIV/AIDS patients still in low PA levels, which does not meet the recommendations for PA levels, as outlined in the 2020 Global Recommendations on Physical Activity for Health, and is similar to the other finding. 14 , 15 , 29 This shows that PA levels of HIV/AIDS patients should be taken care of, and PA levels are affected by different factors, including gender, T-CD4 + cells count, self-efficacy, and perceived barriers, based on study findings.…”
Section: Discussionmentioning
confidence: 67%
“…[9][10][11][12] Until now, there are still a considerable number of HIV/AIDS patients who are not physically active enough to meet the WHO-recommended level of physical activity. [13][14][15] Lower levels of PA may be associated with older age, lower education levels, lower T-CD4 + cells count, exposure to antiviral therapy, mental state, and self-efficacy. 16,17 There are few studies on estimating the level of physical activity and its associated factors in Chinese HIV/AIDS patients.…”
Section: Introductionmentioning
confidence: 99%
“…Apenas 4,9% (n=6) do registros encontrados afirmam a realização de atividade física. Fato preocupante, ao considerar que a maioria das PVHIV em uso de TARV apresentam baixos níveis de atividade física (BERNAL et al, 2022;KITILYA et al, 2022;TAGENE et al, 2022), e que o comportamento sedentário aumenta o risco de alterações metabólicas (BERNAL et al, 2022;TAGENE et al, 2022).…”
Section: Variáveis Comportamentais E Alterações Metabólicas Em Pessoa...unclassified